Ecological Transition: What It Is and How to Do It, Community Technoscience and Green Democracy - Papadopoulos, Dimitris (Tecnoscienza – Italian Journal of Science & Technology Studies, 2021)
The paper examines different practices, imaginaries and programs of ecological transitions whose articulation points towards a more-than-local and less-than-global green eco-social transformation. Translocal ecological transitions bring together climate action politics, environmental justice, and the everyday ecologism of experimental community-led technoscience. Within transition projects we see the emergence of new more-than-human political constituencies, the making of broad eco-social coalitions, and the implementation of innovative forms of reparative governance. Ecological transitions foster a new political space, green democracy, as an alternative to both regressive nationalism and green globalism that dominate contemporary politics.